The Effect Of Cone Drills Training Models On Ball Dribbling Skills In Students Of The Sman 2 Seluma Futsal Extracurricular Program - Pranoto, Rizki Tri; Banat, Azizatul; Apriansyah, Dolly (Journal of Education, 2025)
This study aims to determine the effect of the Cone Drills training model on dribbling skills in futsal extracurricular students of SMAN 2 Seluma. The type of research used in this study is quantitative with experimental methods. The type of experimental research used in this study is Pre-Experimental Design with the One-Group Pretest-Posttest type. This research was conducted at SMAN 2 Seluma in futsal extracurricular students with a population of 15 students. Furthermore, the data analysis technique used in this study is quantitative data analysis. The results of this study obtained the results of the pretest data obtained the fastest or very good dribbling time is 12.09 seconds. and then a posttest test has been carried out which gets the fastest dribbling time or the very good category is 09.11 seconds, also the slowest time or the very bad category when the pretest is 20.25 seconds and the posttest is 20.09 seconds. can be seen from the results of the hypothesis t test above after the t test is carried out. Calculate the hypothesis gets a value of t = 0.03 and t. Table = 2, so the hypothesis is accepted. Therefore, it can be concluded that the cone drills training model has an effect on dribbling skills in futsal extracurricular students at SMAN 2 Seluma.